2021
DOI: 10.1021/acssuschemeng.1c05236
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Energy and Greenhouse Gas Emissions Embodied in Global Primary Plastic Trade Network

Abstract: We present a model of the global primary plastic trade network (GPPTN) and report estimates of embodied impacts including greenhouse gas (GHG) emissions, cumulative fossil energy demand, and embedded carbon. The network is constructed for 11 thermoplastic resins that account for the majority of global primary plastic trade. A total of 170 million metric tonnes (Mt) of primary plastics were traded in 2018, responsible for 350 Mt of embodied GHG emissions, 8.9 exajoules (EJ) of cumulative fossil energy demand an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…They found that after the mid-1990s, PE waste essentially flowed from developed economies (mainly the EU and the USA) to developing economies such as China. Zappitelli et al (2021) explored the global trade structure of primary plastic and reported estimates of specific impacts, including greenhouse gas emissions, cumulative fossil energy demand, and embedded carbon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that after the mid-1990s, PE waste essentially flowed from developed economies (mainly the EU and the USA) to developing economies such as China. Zappitelli et al (2021) explored the global trade structure of primary plastic and reported estimates of specific impacts, including greenhouse gas emissions, cumulative fossil energy demand, and embedded carbon.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Backbone extraction has a wide range of applications. One uses it for various types of networks, such as social 68 – 76 , biological 77 , brain 78 – 81 , gene 82 – 86 , metabolic 87 – 91 , food web 92 , 93 , environmental 94 , 95 , finance 96 – 99 , trade 100 104 , information 105 108 , political 109 , 110 , transportation 111 – 115 , and others 116 119 . These applications have a broad range of uses, including clustering, classification, community detection, outlier detection, pattern set mining, identification of sources of infection in large graphs, and visualization, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Backbone extraction has a wide range of applications. One uses it for various types of networks, such as social [61][62][63][64][65][66][67][68][69] , biological 70 , brain [71][72][73][74] , gene [75][76][77][78][79] , metabolic [80][81][82][83][84] , food web 85,86 , environmental 87,88 , finance [89][90][91][92] , trade [93][94][95][96][97] , information [98][99][100][101] , political 102,103 , transportation [104][105][106][107][108] , and others [109][110]…”
Section: Introductionmentioning
confidence: 99%